Preparation method of waterproof and moisture-permeable film with high temperature resistance and high wear resistance
Patent Information
- Application Number
- CN202510834748.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-20
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-06-20
AI Technical Summary
这导致应力集中于基体表面,使其被迅速磨损,而增强纤维因未能被有效锚固而无法发挥其应有的增强和承载作用,最终使得防水透湿膜整体的耐磨寿命远低于预期
[0019]技术方案一的制备方法通过对防水透湿膜形成过程进行精确的时序性控制,从根本上解决了现有湿法成膜工艺中因界面结合弱而导致的耐高温和耐磨性能不足的问题。该方法首先在步骤一中设定了发生界面化学反应的物质基础,即表面具有活性基团的纤维骨架与包含聚氨酯树脂的铸膜液。
Smart Images

Figure CN120662154B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of waterproof and breathable membrane technology, specifically to a method for preparing a high-temperature resistant and highly abrasion-resistant waterproof and breathable membrane. Background Technology
[0002] In the manufacture of functional waterproof and breathable membranes, to balance the mechanical properties and functional characteristics of the material, a common approach is to fill a porous reinforcing fiber skeleton with a polymer casting solution, and then use a non-solvent-induced phase separation (NIPS) method to cause phase separation of the polymer, thereby forming a waterproof and breathable membrane with a microporous structure. This method is known in the field as a wet film-forming process.
[0003] In traditional wet film-forming processes, the following steps are typically involved: uniformly filling the pores of a reinforcing fiber skeleton with a casting solution containing polymer and solvent; then immersing the entire composite in a single coagulation bath containing a non-solvent. In the coagulation bath, the solvent in the casting solution undergoes rapid diffusion exchange with the non-solvent in the coagulation bath, causing the polymer's solubility to decrease rapidly and precipitate from the solution, thereby forming a polymer matrix with a microporous structure within the pores of the reinforcing skeleton.
[0004] However, the interface between the polymer matrix and the reinforcing fiber skeleton in high-performance waterproof and breathable membranes prepared using existing technologies relies primarily on weak physical entanglement and van der Waals forces, lacking stable and robust covalent bonds. This physically weak interface leads to significant deficiencies in the high-temperature resistance and abrasion resistance of existing waterproof and breathable membranes. Specifically, during subsequent processing requiring heat treatment (such as hot-press bonding of shoe materials) or use in high-temperature environments, interfacial stress arises between the polymer matrix and the reinforcing skeleton due to their different coefficients of thermal expansion. Because the interfacial strength of the physical bond is extremely low, it cannot effectively withstand and transfer this stress, resulting in microscopic delamination and even macroscopic delamination at the interface, causing the waterproof and breathable membrane to lose its structural integrity and functionality. Furthermore, the abrasion resistance of a material depends on the ability of all its components to synergistically resist external friction. In waterproof and breathable membranes with weak interfaces, when the surface is subjected to friction, stress cannot be effectively transferred from the softer polymer matrix to the high-strength reinforcing fibers through a strong interface. This causes stress to concentrate on the substrate surface, causing it to wear down rapidly. The reinforcing fibers, unable to be effectively anchored, cannot perform their intended reinforcement and load-bearing functions, ultimately resulting in the overall abrasion resistance of the waterproof and breathable membrane being far below expectations.
[0005] Therefore, improving the high-temperature resistance and abrasion resistance of functional waterproof and breathable membranes prepared by wet film-forming processes is a key technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] The purpose of this invention is to overcome the above-mentioned defects or problems in the background art and provide a method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane, which can improve the high-temperature resistance and wear resistance of the waterproof and breathable membrane prepared by the wet film-forming process.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] Technical Solution 1: A method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane, comprising the following steps: Step 1: Filling the pores of a fiber skeleton with active groups on its surface with a casting solution containing polyurethane resin and solvent to form a composite; Step 2: Immersing the composite in a first liquid environment composed of ethanol and ethyl acetate to form a covalent bond interface between the fiber skeleton and the polyurethane resin; Step 3: Immersing the composite treated in Step 2 in a second liquid environment composed of water and dimethylformamide to form a polyurethane matrix with a microporous structure in the pores of the skeleton.
[0009] Technical Solution 2 based on Technical Solution 1: In the second liquid environment, the volume content of water is 65% to 75%.
[0010] Technical Solution 3 based on Technical Solution 1: Step 2 is carried out at a temperature of 20-40℃.
[0011] Technical Solution Four based on Technical Solution One: Step Three is carried out at a temperature of 5-10℃.
[0012] Technical Solution 5 based on Technical Solution 1: The fiber skeleton is a high-temperature resistant nanofiber skeleton, and its material is selected from polyimide, poly(p-phenylenebenzodioxazole) fiber, or polybenzimidazole.
[0013] Technical Solution Six based on Technical Solution One: The active group is an amino or carboxyl group introduced onto the surface of the polyimide or poly(p-phenylene benzodioxazole) fiber via a surface modification process, or is a secondary amine group inherent in the polybenzimidazole material.
[0014] Technical solution seven based on technical solution one: The polyurethane resin is a bio-based polyurethane resin.
[0015] Technical solution eight based on technical solution one: The casting solution contains alumina particles and cellulose nanofibers.
[0016] Technical Solution Nine based on Technical Solution One: The filling in Step One is cast onto the fiber skeleton through an adhesive curtain and uniformly permeated by vacuum suction.
[0017] Technical solution ten based on technical solution one: After step three, the method further includes a post-curing treatment of the formed waterproof and breathable membrane, wherein the post-curing treatment is selected from hot air drying, hot pressing or vacuum hot air drying.
[0018] As can be seen from the above description of the present invention, compared with the prior art, the present invention has the following beneficial effects:
[0019] The preparation method of technical solution one fundamentally solves the problem of insufficient high-temperature resistance and wear resistance caused by weak interfacial bonding in existing wet film-forming processes by precisely controlling the timing of the waterproof and breathable membrane formation process. This method first establishes the material basis for the interfacial chemical reaction in step one, namely, a fiber skeleton with active groups on its surface and a casting solution containing polyurethane resin.
[0020] The core of this method lies in step two, immersing the composite in a first liquid environment composed of a mixture of ethanol and ethyl acetate. This liquid environment is a weak non-solvent system for polyurethane resin, and its key function is to significantly slow down the rate of the physical process of macroscopic phase separation and precipitation of polyurethane resin due to solvent exchange. This reduction in rate creates a necessary reaction window for interfacial chemical reactions, allowing sufficient time for the active groups on the fiber skeleton surface to react chemically with the functional groups on the polyurethane resin molecular chains, thereby forming a stable and robust covalent interface between them. This step alters the bonding properties of the interface, transforming the physically weak interface, which is not heat-resistant and abrasion-resistant in existing technologies, into a chemically strong interface capable of effectively withstanding and transmitting stress.
[0021] After establishing a robust chemical interface in step two, step three involves immersing the composite in a second liquid environment composed of a mixture of water and dimethylformamide. This liquid environment is a strong non-solvent system for the polyurethane resin, capable of driving vigorous and rapid phase separation of the polyurethane. Because the interface is pre-locked by covalent bonds and is resistant to disruption by violent physical processes, this step can efficiently form a permeable microporous structure with specific functions without compromising the interfacial bonding strength.
[0022] Through the orderly implementation of the above three steps, the functional waterproof and breathable membrane prepared by this technical solution has a strong interface bonded by covalent bonds. This strong interface enables the waterproof and breathable membrane to effectively withstand and disperse interfacial stress caused by different coefficients of thermal expansion when subjected to heat treatment or high-temperature environments, thereby inhibiting microscopic delamination and macroscopic delamination of the interface and significantly improving the high-temperature resistance of the material. At the same time, this strong interface also enables the waterproof and breathable membrane to effectively transfer stress from the softer polyurethane matrix to the high-strength fiber skeleton when subjected to external friction, achieving synergistic load-bearing of the various components of the material, avoiding rapid wear caused by stress concentration on the matrix surface, and thus significantly improving the wear resistance of the material.
[0023] Technical Solution Two, building upon Technical Solution One, further limits the volume content of water in the second liquid environment to 65% to 75%. This limitation is crucial to the overall performance of the final waterproof and breathable membrane. Precisely controlling the water volume content within this range is key to achieving a rapid yet controlled phase separation process, ensuring the stable formation of a uniform, finger-like microporous network that extends from the surface to the interior. This uniform, defect-free microporous network not only forms the structural basis for the high permeability and excellent waterproof performance of the waterproof and breathable membrane, but its complete structural morphology also avoids stress concentration points caused by internal defects. This enhances the structural stability of the waterproof and breathable membrane under thermal cycling or mechanical friction, providing structural protection for the material's high-temperature resistance and abrasion resistance.
[0024] Technical Solution Three, building upon Technical Solution One, further limits the temperature of step two to 20-40℃. This temperature range allows for precise control of the interfacial chemical reaction kinetics, directly impacting the quality and integrity of the covalent bond interface formation. Within this defined temperature range, optimal activation energy is provided for the reaction between the active groups on the fiber skeleton surface and the polyurethane functional groups. This optimal reaction temperature range of 20-40℃ is a crucial process condition ensuring the efficient, complete, and specific formation of interfacial covalent bonds. A more complete and robust covalent bond interface translates to stronger interfacial bonding strength, providing the strongest guarantee for the waterproof and breathable membrane to ultimately achieve excellent high-temperature resistance and abrasion resistance.
[0025] Technical Solution Four, building upon Technical Solution One, further limits the temperature in step three to 5-10℃. This limitation represents a further optimization of the nucleation and growth kinetics during rapid phase separation. In a strongly non-solvent system, lower temperatures significantly increase the supersaturation of the polymer solution, thereby greatly increasing the nucleation rate and facilitating the formation of smaller, more uniformly distributed microporous structures. This highly uniform microstructure improves the consistency of the final product's macroscopic properties and reduces weak points within the material. This structural uniformity is crucial for improving the material's durability, as it enhances the material's resistance to localized stress concentration, thus contributing to improved structural stability of the waterproof and breathable membrane under high-temperature environments and its wear resistance under long-term friction.
[0026] Technical Solution Five, building upon Technical Solution One, further limits the fiber skeleton material to polyimide, poly(p-phenylenebenzodioxazole) fiber, or polybenzimidazole. These selected materials are all high-performance specialty polymer fibers, forming the cornerstone of the entire waterproof and breathable membrane's high-temperature resistance and high abrasion resistance. The glass transition temperature and thermal decomposition temperature of these fiber materials are significantly higher than those of conventional polymers, ensuring that the skeleton itself will not soften or degrade under high-temperature conditions, providing stable structural support for the waterproof and breathable membrane. Furthermore, these materials possess extremely high tensile modulus and strength; under the strong interfacial action of this invention, they can serve as the primary load-bearing units, thereby endowing the final product with excellent overall mechanical properties, which is fundamental to achieving high abrasion resistance.
[0027] Technical Solution Six, building upon Technical Solution Five, further clarifies the source of the active groups. This limitation is a prerequisite for ensuring the interfacial chemical bonding described in Technical Solution One is realized, clearly elucidating the specific chemical pathway for forming the covalent bond interface. By specifying the specific chemical mechanism for covalent bond formation, not only is the logical rigor and technical reliability of this technical solution greatly enhanced, but the resulting interfacial covalent bonds also exhibit higher density and stronger binding force. A strong interface with a clear and reliable chemical mechanism is a direct guarantee for the excellent high-temperature resistance and wear resistance of the waterproof and breathable membrane.
[0028] Technical Solution Seven, building upon Technical Solution One, further limits the type of polyurethane resin to bio-based polyurethane resin. The core value of this limitation lies in its ability to endow the product with green, environmentally friendly, and sustainable development attributes while ensuring all high-performance indicators of the waterproof and breathable membrane. This invention demonstrates that its core gradient coagulation bath process is also applicable to bio-based polymer systems. This results in a high-temperature resistant, high-abrasion-resistant waterproof and breathable membrane that not only meets stringent functional requirements but also aligns with the inevitable global trend of manufacturing transformation towards green and low-carbon practices, thereby enhancing the product's market competitiveness and social value.
[0029] Technical Solution 8, building upon Technical Solution 1, further incorporates alumina particles and cellulose nanofibers into the casting solution. This limitation introduces a multi-scale reinforcing phase, constructing a more complex composite reinforcement system, thereby improving the material's wear resistance and high-temperature resistance in multiple dimensions. Alumina, as a high-hardness, high-thermal-stability inorganic ceramic particle, can directly act as wear-resistant hard points in the polyurethane matrix, preferentially bearing and resisting external wear when the material surface is subjected to friction, significantly improving the waterproof and breathable membrane's scratch resistance and wear life. Simultaneously, cellulose nanofibers, as a nanoscale reinforcement, can form a fine reinforcing network within the polyurethane matrix, enhancing the matrix's cohesive strength and toughness, thus creating a multi-scale synergistic reinforcement effect with the fiber skeleton, further improving the overall mechanical strength and fatigue resistance of the waterproof and breathable membrane.
[0030] Technical Solution Nine, building upon Technical Solution One, further specifies the filling method in Step One: casting using a sizing curtain combined with vacuum suction. This limitation optimizes and ensures the process, a crucial prerequisite for obtaining high-quality products. This combination effectively solves common process defects such as uneven filling and residual air bubbles. A defect-free, uniform composite is the foundation for the success of all subsequent steps, ensuring continuous and complete covalent bond interfaces and a uniform microporous structure. This structural integrity avoids stress concentration caused by defects, which is essential for ensuring the reliability of the final product under high-temperature and wear conditions, providing a process guarantee for its excellent high-temperature and wear-resistant properties.
[0031] Technical Solution Ten, building upon Technical Solution One, adds a post-curing treatment step. This step is an indispensable final stage in the transformation of the waterproof and breathable membrane from laboratory preparation to industrial-grade finished product, crucial for ensuring the stability and durability of the product's performance. Through post-curing, residual solvents in the waterproof and breathable membrane can be effectively removed, internal stresses generated during film formation can be released, and the microporous structure can be locked in. Only a waterproof and breathable membrane free of residual solvents, internal stresses, and structural stability can maintain its dimensional stability and mechanical properties under high-temperature environments and exhibit consistent wear resistance under long-term friction. Therefore, post-curing is a necessary step to ensure the stable and long-lasting high-temperature resistance and wear resistance of the waterproof and breathable membrane. Attached Figure Description
[0032] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments are briefly introduced. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0033] Figure 1 Image 1 is a scanning electron microscope image of the waterproof and breathable membrane prepared in Example 1 of the present invention;
[0034] Figure 2 Image 2 is a scanning electron microscope image of the waterproof and breathable membrane prepared in Example 1 of this invention;
[0035] Figure 3 Image 3 is a scanning electron microscope image of the waterproof and breathable membrane prepared in Example 1 of the present invention. Detailed Implementation
[0036] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are preferred embodiments of the present invention and should not be considered as excluding other embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0037] Unless otherwise expressly defined, the use of terms such as "first," "second," or "third" in the claims, description, and accompanying drawings of this invention is for distinguishing different objects and not for describing a specific order.
[0038] Unless otherwise expressly defined, in the claims, description, and accompanying drawings of this invention, the use of directional terms such as "center," "lateral," "longitudinal," "horizontal," "vertical," "top," "bottom," "inner," "outer," "upper," "lower," "front," "rear," "left," "right," "clockwise," and "counterclockwise" to indicate orientation or positional relationships is based on the orientation and positional relationships shown in the accompanying drawings and is only for the convenience of describing the invention and simplifying the description, and is not intended to indicate or imply that the device or element referred to must have a specific orientation or be constructed and operated in a specific orientation, and therefore should not be construed as limiting the specific scope of protection of this invention.
[0039] Unless otherwise expressly defined, the terms "fixed connection" or "fixed connection" used in the claims, description and drawings of this invention should be interpreted broadly to refer to any connection in which there is no displacement or relative rotation relationship between the two parties, including non-removable fixed connection, detachable fixed connection, integral connection and fixed connection by other means or components.
[0040] In the claims, description and accompanying drawings of this invention, the terms "comprising," "having," and variations thereof are used to mean "including but not limited to."
[0041] This invention relates to a method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane, comprising the following steps: Step 1: Filling the pores of a fiber skeleton with active groups on its surface with a casting solution containing polyurethane resin and solvent to form a composite; Step 2: Immersing the composite in a first liquid environment composed of ethanol and ethyl acetate to form a covalent bond interface between the fiber skeleton and the polyurethane resin; Step 3: Immersing the composite treated in Step 2 in a second liquid environment composed of water and dimethylformamide to form a polyurethane matrix with a microporous structure in the pores of the skeleton.
[0042] In the second liquid environment, the water volume content is 65% to 75%. Step two is performed at a temperature of 20-40°C. Step three is performed at a temperature of 5-10°C. Specifically, in a preferred embodiment, the temperature of the first liquid environment is 25°C, the temperature of the second liquid environment is 5°C, and the water volume content in the second liquid environment is 70%.
[0043] Furthermore, the fiber skeleton is a high-temperature resistant nanofiber skeleton, and its material is selected from polyimide, poly(p-phenylenebenzodioxazole) fiber, or polybenzimidazole. Specifically, the porosity of the high-temperature resistant nanofiber skeleton is 70-95%, and its average pore size is 10-500 nm, to ensure that the casting solution can fully penetrate and provide sufficient space for the final microporous structure.
[0044] The active groups are amino or carboxyl groups introduced onto the surface of the polyimide or poly(p-phenylenebenzodioxazole) fibers via a surface modification process, or are secondary amine groups inherent in the polybenzimidazole material. Specifically,
[0045] The polyurethane resin is a bio-based polyurethane resin. Specifically, to introduce amino groups, the polyimide nanofiber membrane can be immersed in a 5% (w / w) solution of 3-aminopropyltriethoxysilane (APTES) in ethanol and treated at 60°C for 30 minutes; to introduce carboxyl groups, the poly(p-phenylenebenzodioxazole) fiber can be immersed in a 65% (w / w) concentrated nitric acid and oxidized at 80°C for 1 hour. The bio-based polyurethane resin, as determined according to ASTM D6866, has a bio-based content of not less than 60%. This resin is prepared by reacting a bio-based polyester polyol (such as that obtained by condensation polymerization of bio-based succinic acid and bio-based 1,4-butanediol) with diphenylmethane diisocyanate (MDI).
[0046] The casting solution contains alumina particles and cellulose nanofibers. Specifically, the casting solution is prepared by uniformly mixing bio-based polyurethane resin, alumina particles (average particle size 50-100 nm) accounting for 1.0%-3.0% of the total dry weight of the resin, cellulose nanofibers accounting for 0.5%-2.0% of the total dry weight of the resin, and penetrant OT-50 (sodium dioctyl succinate sulfonate) accounting for 0.1%-0.5% of the total dry weight of the resin in dimethylformamide (DMF) as the main solvent.
[0047] In step one, the filling process involves casting the casting solution onto the fiber skeleton using a sizing curtain and achieving uniform penetration through vacuum suction. Specifically, this filling step uses a sizing curtain with a slit width of 0.5 mm to uniformly coat the surface of the fiber skeleton with the casting solution. Simultaneously, vacuum assistance is applied to the other side of the skeleton, controlling the absolute pressure of the system within the range of 20 kPa to 50 kPa, to ensure that the casting solution rapidly and without bubbles penetrates into the internal pores of the skeleton.
[0048] Furthermore, after step three, the method further includes a post-curing treatment of the formed waterproof and breathable membrane, wherein the post-curing treatment is selected from hot air drying, hot pressing, or vacuum hot air drying. Specifically, hot air drying can be performed at 80°C for 2 minutes; hot pressing can be performed at 90°C and 0.5 MPa pressure for 3 minutes; and vacuum hot air drying can be performed at 70°C for 5 minutes.
[0049] The present invention relates to a method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane. By precisely controlling the timing of the membrane formation process, this method fundamentally solves the problem of insufficient high-temperature resistance and wear resistance caused by weak interfacial bonding in existing wet film-forming processes. The method first establishes the material basis for the interfacial chemical reaction in step one: a fiber skeleton with active groups on its surface and a casting solution containing polyurethane resin. The core of this method lies in step two, immersing the composite in a first liquid environment composed of a mixture of ethanol and ethyl acetate. This liquid environment is a weak non-solvent system for polyurethane resin, and its key function is to significantly slow down the rate of macroscopic phase separation and precipitation of polyurethane resin due to solvent exchange. This reduction in rate creates a necessary reaction window for the interfacial chemical reaction, allowing sufficient time for the active groups on the fiber skeleton surface to react chemically with the functional groups on the polyurethane resin molecular chains, thereby forming a stable and strong covalent bond interface between them. This step changes the bonding properties of the interface, transforming the physically weak interface (lacking heat and wear resistance in existing technologies) into a chemically strong interface capable of effectively withstanding and transmitting stress. After establishing a robust chemical interface in step two, step three involves immersing the composite in a second liquid environment composed of a mixture of water and dimethylformamide. This liquid environment is a strong non-solvent system for polyurethane resin, capable of driving vigorous and rapid phase separation of the polyurethane. Since the interface is pre-locked by covalent bonds and is resistant to damage from violent physical processes, this step efficiently forms a permeable microporous structure with specific functions without compromising the interfacial bonding strength. Through the orderly implementation of these three steps, the functional waterproof and breathable membrane prepared by this technical solution possesses a strong interface bonded by covalent bonds. This strong interface allows the waterproof and breathable membrane to effectively withstand and disperse interfacial stresses caused by differences in thermal expansion coefficients when subjected to heat treatment or high-temperature environments, thereby suppressing microscopic delamination and macroscopic delamination of the interface and significantly improving the material's high-temperature resistance. At the same time, this strong interface also enables the waterproof and breathable membrane to effectively transfer stress from the softer polyurethane matrix to the high-strength fiber skeleton when subjected to external friction, achieving synergistic load-bearing of the material components and avoiding rapid wear caused by stress concentration on the matrix surface, thereby significantly improving the wear resistance of the material.
[0050] To further illustrate the superiority of the technical solution of the present invention, the following embodiments and comparative examples are provided.
[0051] Raw materials used in the examples
[0052] Polyimide (PI) nanofiber skeleton: purchased from Jiangsu Shunyi Composite Materials Co., Ltd., China, grade SY-PI-NFM-20, porosity 85%, average pore size 200nm.
[0053] Poly(p-phenylenebenzodioxazole) nanofiber skeleton: purchased from Toyobo Co., Ltd., Japan, brand name [not specified]. AS is a framework with a porosity of 80% and an average pore size of 300nm, produced by laboratory electrospinning.
[0054] Polybenzimidazole (PBI) nanofiber skeleton: purchased from PBI Performance Products, Inc., USA, brand name: PBI was produced by laboratory electrospinning to create a framework with a porosity of 90% and an average pore size of 400 nm.
[0055] Bio-based polyurethane (BPU) resin: purchased from Wanhua Chemical Group Co., Ltd., China, brand name: WHT-B85A is a DMF solution with 62% bio-based content and 30% solid content.
[0056] 3-Aminopropyltriethoxysilane (APTES): Purchased from Dow Chemical Company, USA, brand name DOWSIL TM Z-6011Silane.
[0057] Alumina (Al2O3) particles: purchased from Aladdin Biochemical Technology Co., Ltd. of China, grade A108848, spherical, with an average particle size of 80nm.
[0058] Cellulose nanofibers (CNC): purchased from China Zhongke Xianxing (Suzhou) Nanotechnology Co., Ltd., brand name XFN-CNC-01, 5% aqueous dispersion.
[0059] Penetrant OT-50: Purchased from BASF, Germany, brand name [not specified]. A-BO.
[0060] Other reagents: Ethanol, ethyl acetate, dimethylformamide (DMF), and concentrated nitric acid were all of analytical grade and purchased from China National Pharmaceutical Group Chemical Reagent Co., Ltd.
[0061] Example 1
[0062] This embodiment relates to a method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane, the specific steps of which are as follows:
[0063] Step 1: The casting solution containing polyurethane resin and solvent is filled into the pores of the fiber skeleton with active groups on the surface to form a composite.
[0064] First, the PI nanofiber skeleton underwent surface modification treatment: the PI nanofiber skeleton was immersed in a 5% (w / w) APTES ethanol solution and stirred at 60°C for 30 minutes to graft amino active groups onto the fiber surface. After removal, it was washed three times with anhydrous ethanol and then dried in a vacuum oven at 60°C for 2 hours.
[0065] Next, the casting solution is prepared: 1.5 parts of Al2O3 particles, 1 part of water-dispersed CNC (converted to dry weight), and 0.2 parts of penetrant OT-50 are added to 100 parts of BPU resin solution and mixed evenly under high-speed stirring to obtain the casting solution.
[0066] Finally, filling is performed: using a sizing curtain with a slit width of 0.5 mm, the casting solution is uniformly coated on the surface of the modified PI fiber skeleton, while vacuum assistance is applied on the other side of the skeleton to control the absolute pressure of the system at 30 kPa to achieve uniform penetration.
[0067] Step 2: Immerse the composite in a first liquid environment composed of a mixture of ethanol and ethyl acetate to form a covalent interface between the fiber skeleton and the polyurethane resin.
[0068] The composite obtained in step one is immersed in a first liquid environment consisting of a mixture of ethanol and ethyl acetate in a volume ratio of 3:1, and treated in this liquid environment at a temperature of 25°C for 2 minutes.
[0069] Step 3: Immerse the composite treated in Step 2 into a second liquid environment composed of water and dimethylformamide to form a polyurethane matrix with a microporous structure in the pores of the skeleton.
[0070] The composite treated in step two was immediately immersed in a second liquid environment consisting of a mixture of water and DMF in a volume ratio of 7:3, and treated in this liquid environment at a temperature of 5°C for 3 minutes.
[0071] Step 4: Perform post-curing treatment on the formed waterproof and breathable membrane.
[0072] The wet film obtained in step three is dried in a hot air circulating oven at 80°C for 2 minutes to obtain the final high-temperature resistant, high-wear resistant, waterproof and breathable membrane.
[0073] Example 2
[0074] This embodiment is basically the same as Embodiment 1, except that:
[0075] In step one, PBO nanofiber framework is used. The surface modification process is as follows: the PBO nanofiber framework is immersed in 65% concentrated nitric acid and oxidized at 80°C for 1 hour to introduce carboxyl active groups onto the fiber surface. After removal, it is repeatedly washed with a large amount of deionized water until the washing solution is neutral, and then dried in a vacuum oven at 80°C.
[0076] The post-curing treatment in step four is as follows: hot pressing at 90℃ and 0.5MPa for 3 minutes.
[0077] Example 3
[0078] This embodiment is basically the same as Embodiment 1, except that:
[0079] In step one, PBI nanofiber framework is used because its molecular structure contains secondary amine active groups, so no additional surface modification treatment is required.
[0080] The first liquid environment in step two is a mixture of ethanol and ethyl acetate in a volume ratio of 4:1, and the treatment temperature is 20°C.
[0081] The second liquid environment in step three is a mixture of water and DMF in a volume ratio of 6.5:3.5, and the treatment temperature is 10°C.
[0082] Comparative Example 1
[0083] This comparative example is used to illustrate the necessity of the gradient coagulation bath process of the present invention.
[0084] The preparation method is basically the same as in Example 1, except that step two is skipped. That is, after completing step one, the composite is directly immersed in a second liquid environment consisting of water and DMF mixed in a volume ratio of 7:3, treated at 5°C for 3 minutes in this liquid environment, and then subjected to the same post-curing treatment.
[0085] Comparative Example 2
[0086] This comparative example is used to illustrate the necessity of surface-active groups on the fiber skeleton.
[0087] The preparation method is basically the same as in Example 1, except that the PI nanofiber framework used in step one has not undergone any surface modification treatment, that is, its surface does not have grafted amino active groups. All other steps are exactly the same as in Example 1.
[0088] Performance Tests and Results
[0089] The performance of the waterproof and breathable membranes prepared in Examples 1-3 and Comparative Examples 1-2 was tested. The test methods and results are shown in the table below.
[0090] Testing standards:
[0091] 1. Interface bonding strength: Refer to GB / T 2790-1995 (Test method for peel strength of adhesives at 180°, flexible materials to rigid materials) to conduct a peel test on the PU matrix and fiber skeleton.
[0092] 2. High temperature resistance (appearance after 180℃ heat treatment): Place the sample in an oven at 180℃ for 30 minutes, remove it and cool it to observe the changes in its appearance, and evaluate whether there are phenomena such as delamination, blistering, and shrinkage.
[0093] 3. Abrasion resistance (mass loss): Refer to GB / T 10408-2000 (Taber method for testing abrasion of plastics), use CS-10 grinding wheel, apply a load of 1000g, and test the mass loss after 1000 cycles.
[0094] 4. Water vapor transmission rate: Refer to GB / T 12704.2-2009 (Textiles - Test Methods for Moisture Permeability of Fabrics - Part 2:
[0095] The test was conducted using the evaporation method at 38°C and 90% RH.
[0096] 5. Hydrostatic pressure: Refer to GB / T 4744-2013 (Test and evaluation of waterproof performance of textiles - hydrostatic pressure method).
[0097] Performance test results table:
[0098]
[0099] As can be seen from the data in the table above, the waterproof and breathable membranes prepared in Examples 1-3 have significantly higher interfacial bonding strength than those in Comparative Examples 1 and 2, demonstrating that the gradient coagulation bath process and the addition of surface-active groups in this invention can significantly enhance interfacial bonding. Consequently, the samples in Examples 1-3 maintained their structural integrity and exhibited excellent wear resistance and minimal mass loss after being subjected to a high-temperature treatment at 180°C, fully demonstrating that this invention can effectively solve the problems of insufficient high-temperature resistance and wear resistance pointed out in the background art.
[0100] Comparative Example 1 lacked the crucial step of forming a covalent bond interface, resulting in extremely weak interfacial bonding and severe delamination at high temperatures, leading to the worst wear resistance. Although Comparative Example 2 used a gradient coagulation bath, the absence of active groups on the skeleton surface prevented the formation of effective chemical bonds. While its performance was superior to Comparative Example 1, it was still far inferior to the embodiments of the present invention.
[0101] In addition, all samples maintained excellent waterproof and breathable properties, indicating that the present invention has not sacrificed the original core functions of the material while significantly improving high temperature resistance and wear resistance.
[0102] In addition, Figure 1 , 2 Images 1 and 3 are scanning electron microscope (SEM) images of the waterproof and breathable membrane prepared using Example 1 of the present invention. They visually demonstrate from the microstructure that the present invention can achieve the above-mentioned excellent technical effects.
[0103] Appendix Figure 2 and attached Figure 3 This is a cross-sectional view of the waterproof and breathable membrane. The image clearly shows that the polyurethane matrix has completely and uniformly penetrated and filled the pores of the fiber skeleton. Most importantly, the polyurethane matrix and each individual nanofiber are tightly bonded, forming a seamless, gapless interface. This microstructure is a direct manifestation of the covalent bond interface preferentially formed in step two of this invention. Because of this strong chemical interface, when the material undergoes a peel test, the destructive force is difficult to easily propagate along the interface, thus exhibiting extremely high interfacial bonding strength (e.g., 25.8 N / 25 mm in Example 1). Similarly, when subjected to a high-temperature treatment at 180°C, this defect-free strong interface can effectively withstand and transmit the interfacial stress caused by the different coefficients of thermal expansion, avoiding the generation and propagation of microcracks, resulting in a macroscopic appearance of "intactness and no change." In contrast, Comparative Examples 1 and 2 lack this strong interface, and their interfaces have numerous micro-defects, which easily expand into macroscopic delamination and peeling under thermal stress.
[0104] Appendix Figure 2 and attached Figure 3 The complete and dense composite structure shown explains the material's excellent wear resistance. Under friction, external stress can be effectively transferred from the softer polyurethane matrix to the high-strength, high-hardness PI fiber skeleton through this seamless, strong interface. The fiber skeleton, as the main load-bearing phase, works synergistically with the matrix to resist external wear. In contrast, in the comparative example, due to the weak interfacial bonding, stress cannot be effectively transferred, causing frictional forces to concentrate on the softer matrix surface, leading to rapid wear and significant mass loss.
[0105] Appendix Figure 1 This is a surface view of the waterproof and breathable membrane. As can be seen from the image, although the polyurethane matrix is filled with a fiber network, the entire membrane surface still maintains an open, porous structure. This provides effective diffusion channels for water vapor molecules, resulting in a high water vapor permeability (e.g., 8550 g / m³ in Example 1). 2 The structural basis of the material is as follows (24h). Meanwhile, the polyurethane matrix formed in step three has a microporous structure with pores much smaller than liquid water droplets, thus effectively preventing the penetration of liquid water and ensuring the material's high hydrostatic pressure performance.
[0106] The foregoing description of the specifications and embodiments is intended to explain the scope of protection of this invention, but does not constitute a limitation on the scope of protection of this invention. Modifications, equivalent substitutions, or other improvements to the embodiments of this invention or a portion thereof that can be obtained by those skilled in the art through logical analysis, reasoning, or limited experimentation, based on the teachings of this invention or the foregoing embodiments, in conjunction with common knowledge, general technical knowledge, and / or existing technology, should all be included within the scope of protection of this invention.
Claims
1. A method for preparing a high-temperature resistant, highly abrasion-resistant, waterproof and breathable membrane, characterized in that, Includes the following steps: Step 1: A casting solution containing polyurethane resin and solvent is filled into the pores of a fiber skeleton with active groups on its surface to form a composite. The fiber skeleton is a high-temperature resistant nanofiber skeleton, and its material is selected from polyimide, poly(p-phenylene benzodioxazole) fiber, or polybenzimidazole. The active groups are amino or carboxyl groups introduced on the surface of the polyimide or poly(p-phenylene benzodioxazole) fiber through a surface modification process, or are secondary amine groups inherent in the polybenzimidazole material. Step 2: Immerse the composite in a first liquid environment composed of a mixture of ethanol and ethyl acetate to form a covalent interface between the fiber skeleton and the polyurethane resin; Step 3: Immerse the composite treated in Step 2 into a second liquid environment composed of water and dimethylformamide to form a polyurethane matrix with a microporous structure in the pores of the skeleton.
2. The method for preparing the high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: In the second liquid environment, the water volume content is 65% to 75%.
3. The method for preparing the high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: Step two is performed at a temperature of 20-40℃.
4. The method for preparing the high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: Step three is performed at a temperature of 5-10℃.
5. The method for preparing the high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: The polyurethane resin is a bio-based polyurethane resin.
6. The method for preparing the high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: The casting solution contains alumina particles and cellulose nanofibers.
7. The method for preparing the high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: The filling in step one is achieved by casting the filling material onto the fiber skeleton through a sizing curtain and then uniformly penetrating it through vacuum suction.
8. The method for preparing the high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: The method further includes a post-curing treatment of the formed waterproof and breathable membrane after step three, wherein the post-curing treatment is selected from hot air drying, hot pressing or vacuum hot air drying.
Citation Information
Patent Citations
High-strength polyurethane waterproof and moisture-permeable film and preparation method thereof
CN111705430A
Bio-based polyurethane waterproof moisture-permeable film and preparation method thereof
CN119083195A